Age and sex differences in IRONMAN World Championship performance - Gries, K. J.; Witto, P. E. (The Journal of Strength and Conditioning Research, 2025)
There has been an increasing number of masters athletes, particularly women, who have been competing in ultra-endurance events. With this in mind, we sought to determine the influence of age and sex on IRONMAN World Championship performances from 2014 to 2023. The final times of each component (swim, bike, and run) and overall time were collected for places 1st to 10th in each age group (18-69 years). Sex differences in performance were calculated for each age group. Depth of field (time of nth place/first place), a surrogate for participation, was also calculated for each age group and sex. Significance was set at p < 0.05. These data show a ~12% sex difference in the performance of the swim, bike, run, and final (p < 0.05), which increased to 20% in the 65-69 years age group (p < 0.05). The differences appeared driven by the bike and run. Depth of field was greater in men than in women (p < 0.05), and the sex difference increased with age. Sex differences in performance trended to be related to depth of field (p = 0.08; R2 = 0.32), suggesting a moderate role of participation in performance sex differences. Although speculative, the performance data can give us an insight into the physiology and sociology of these elite athletes and warrants future research.